OLEOGRANULOMA OF THE BREAST AFTER SECTOR RESECTION: DIAGNOSIS PRINCIPLES AND MANAGEMENT TACTICS - Arif Guseynov; V. Fedorischev; M. D'yakov (Clinical Medicine and Pharmacology, 2026)
The article discusses the problem of mammary glands (MG) oleogranulomas after sectoral resection for benign lesions. The aim of the study is to examine the statistics of postoperative MG after sectoral resection, to assess the current state of their diagnostics and management tactics.154 patients with various focal lesions of the breast were operated on. During the ultrasound of the MG 3 months after surgery, focal formations in the surgical intervention zone were revealed in 26 (16.9%) patients. Among them, oleogranuloma was revealed in 12 (46.2%) patients. The management tactics for patients with oleogranuloma consisted of dy-namic observation of patients with physical examination and ultrasound of the MG every 3 months. Other methods – X-ray mammography, magnetic resonance imaging, and puncture biopsy – were performed on an indication depending on the clinical situation. One year after surgery, there was a positive trend: in 2 cases, the oleogran-ulomas completely resolved.